Characterization of BAM-B4C composites prepared by spark plasma sintering. Issue 8 (15th April 2021) - Riera, Rafael A.; Bavdekar, Salil; DeVries, Matthew; Singh, Jogendar; Subhash, Ghatu
Abstract: Aluminum magnesium boride (BAM) and boron carbide (B4 C) show great promise for engineering applications due to their high strength, hardness, and impact resistance along with low mass density. Four BAM-B4 C composite specimens (100% BAM, BAM + 10 wt% B4 C, BAM + 20 wt% B4 C, and BAM + 50 wt% B4 C) produced by spark plasma sintering were characterized using electron microscopy and energy dispersive spectroscopy. Mechanical properties such as hardness, compressive strength and fracture toughness were experimentally determined under quasistatic and dynamic conditions. It was found that addition of B4 C increased the mechanical properties of the composite. The BAM + 10 wt% B4 C composite possessed the highest compressive strength while the BAM + 20 wt% B4 C composite possessed the highest fracture toughness. Any further addition of B4 C lead to extensive phase segregation and cracking within the composite microstructure, highly degrading its mechanical properties.